Analisis Kebijakan Kenaikan Tarif Tol di Provinsi Riau (Studi Kasus Tol Permai Pekanbaru-Dumai) - Syahputri, Ella; Yuliani, Febri (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the toll tariff increase policy in Riau Province with a case study on the Pekanbaru-Dumai Toll Road. The increase in toll tariffs is an important issue because it has a direct impact on community mobility, logistics costs, and regional economic growth. This study uses a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews with toll road managers, road users, as well as policy analysis and secondary data related to toll rates and vehicle traffic. The results of the study indicate that the tariff increase policy is based on regulations that regulate tariff adjustments every two years based on inflation, but its implementation has not fully considered people's purchasing power and its impact on local economic activities. This study recommends the need for a comprehensive evaluation of the tariff adjustment policy by considering the socio-economic aspects of the community and increasing transparency in the decision-making process.